Peran Mikroorganisme dalam Peningkatan Kesuburan Tanah dan Produktivitas Pertanian: Kajian Literatur - Wince Amsyah Natalia Zai; Natalia Kristiani Lase (Hidroponik : Jurnal Ilmu Pertanian Dan Teknologi Dalam Ilmu Tanaman, 2025)
This research aims to explore the role of soil microorganisms in improving soil fertility and agricultural productivity to support sustainable agriculture. Using the literature review method, various scientific literatures were analyzed to identify the potential, challenges, and optimization strategies of microorganism technology. Microorganisms such as Nitrobacter, Streptomyces sp. and Trichoderma sp. play significant roles in nitrogen cycling, organic matter decomposition and plant pathogen control. In addition to naturally improving soil nutrition, these microorganisms also support agricultural efficiency by reducing dependence on synthetic chemical fertilizers and pesticides. However, the adoption of this technology faces obstacles, such as farmers' lack of knowledge and limited access to quality products. Therefore, strategic steps are needed in the form of training programs, extension, and policy development to support the implementation of microorganism-based technologies. In the context of climate change, microorganisms also contribute to greenhouse gas mitigation and increase crop tolerance to abiotic stress. The results of this study emphasize the importance of microorganisms as a sustainable solution to the challenges of modern agriculture, as well as the need for collaboration between various parties to increase the capacity of farmers in implementing this technology.